An electronic radon dosimeter as a new multipurpose device – a bridge between dosimetry and monitoring - S. Feige; V. Oeser; T. Streil (Geofísica Internacional, 2002)
An electronic radon dosimeter based on deposition of radon decay products on a semiconductor detector coupled with an alpha spectroscopy offers some advantages compared to passive dosimeters. The dose value and the radon concentration is calculated and displayed online during the exposure time and preestablished dose limits can be watched by an alert function. Rapid changes of the radon concentration can be detected and the corresponding dose is available in its time distribution as well. The PC-based dose management provides an administrator desk for stuff planning and enables the change of measurement presets like dose conversion- or equilibrium factor. The standard infrared interface handles the data communication with a PC. The electronic radon dosimeter is, easy to handle and rugged enough to withstand the rough working conditions. A second application of an electronic automated radon dosimeter is monitoring of radon affected objects or areas. The possibility to measure the radon concentration in the soil gas or in water enables the user to solve questions concerning radon risk mapping and risk protection as well as topics in geology, searching for ore deposits or environmental protection.